Critical risk factors in ship fire accidents. Issue 6 (18th August 2021) - Wang, Likun; Wang, Jinhui; Shi, Mingyang; Fu, Shanshan; Zhu, Mo
ABSTRACT: Risk management of ship fire accidents (SFA) is a vital issue in maritime transportation systems since ship fires are instantaneous and developing events-small errors can cause serious accidents. The traditional approach for SFA analysis is on a coarse-grained level, using accident data from one or several case studies or expert knowledge; such data acquisition method substantially relies on subjective expert experience and brings about epistemic uncertainties. This study proposes a new framework for identifying critical risk factors in SFA. First, grounded theory (GT) is applied to obtain risk factors on a fine-grained level by converting unstructured text information to structured accident data. Then, Fault tree analysis (FTA) is used to develop a risk model and make a quantitative analysis of the SFA. Bayesian network (BN) is also integrated to verify and identify the critical risk factors in SFA with sensitivity analysis. Results indicate that sealing off the ship cabin timely, effective ventilation system, as well as prompt emergency response by crews and passengers on board are the dominant factors. Our findings provide useful insights for maritime safety administration and shipping companies to take actions for fire prevention.